Enhanced bio-oil production and fatty acid extraction from pyrolyzed spent coffee ground using Box-Behnken design optimization - Yasser, Tasya Muhamad; Boonyubol, Sasipa; Cross, Jeffrey Scott (International Journal of Chemical and Process Engineering Research, 2025)
The disposal of spent coffee grounds (SCG), a biomass waste generated from coffee brewing, poses a significant environmental concern due to its high organic content and large volume. To address this issue, a valorization approach was undertaken that involved the production of bio-oil from SCG through pyrolysis and the subsequent extraction of oleic acid, the most abundant fatty acid in SCG. A Box-Behnken experimental design was employed to optimize pyrolysis yields using three process parameters: SCG particle size (<0.25, 0.25 – 0.70, 0.70 – 1.70 mm), pyrolysis temperature (500 – 600 °C), and nitrogen flow rate (0.5 – 1.5 L/min). Pyrolysis was conducted in a fixed-bed reactor, and the resulting bio-oil was characterized using gas chromatography. Statistical analysis indicated that all three parameters significantly influenced the bio-oil yield, with temperature and spent coffee grounds (SCG) particle size being the primary factors affecting fatty acid concentration. The optimal conditions identified included an SCG particle size of less than 0.25 mm, a temperature of 550°C, and a nitrogen flow rate of 0.5 L/min, which yielded a bio-oil production of 34.13%. Oleic acid was successfully extracted from the pyrolyzed bio-oil through liquid-liquid extraction using hexane, demonstrating its potential for further chemical processing. These findings illustrate a dual valorization pathway for SCG, enabling the production of both renewable bio-oil and oleic acid as platform bio-based chemicals.